Wavefront Longest Common Subsequence Algorithm On Multicore And Gpgpu Platform. - Shehabat, Bilal Mahmoud (2010)
String comparison is a central operation in numerous applications. It has a critical task in many operations such as data mining, spelling error correction and molecular biology (Tan et al, 2007; Michailidis and Margaritis, 2000).